2020
DOI: 10.1159/000512340
|View full text |Cite
|
Sign up to set email alerts
|

Serum Urate Lowering Therapy Using Allopurinol Improves Serum 25 Hydroxy Vitamin D in Stage 3-5 CKD Patients: A Pilot Study

Abstract: <b><i>Background:</i></b> Recent studies have demonstrated negative associations of serum uric acid (SUA) with serum 25 hydroxy vitamin D (25 [OH] vit D) among CKD patients. <b><i>Objective:</i></b> The aim of the study was to look for the impact of hypouricemic therapy using allopurinol on serum level of 25 (OH) vit D in CKD patients. <b><i>Cases and Methods:</i></b> Seventy-two CKD stage 3–5 patients were selected to this study. Patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…In addition, uric acid might exert adverse effects on bone health by affecting 25-OH-D (1,25D) and parathyroid hormone (PTH) levels. An inverse correlation between 1,25D concentrations and uric acid has been revealed in the HU model and chronic kidney disorder subjects ( 39 41 ). However, this association could be reversed by allopurinol, a drug that lowers uric acid levels ( 41 ).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In addition, uric acid might exert adverse effects on bone health by affecting 25-OH-D (1,25D) and parathyroid hormone (PTH) levels. An inverse correlation between 1,25D concentrations and uric acid has been revealed in the HU model and chronic kidney disorder subjects ( 39 41 ). However, this association could be reversed by allopurinol, a drug that lowers uric acid levels ( 41 ).…”
Section: Discussionmentioning
confidence: 94%
“…An inverse correlation between 1,25D concentrations and uric acid has been revealed in the HU model and chronic kidney disorder subjects ( 39 41 ). However, this association could be reversed by allopurinol, a drug that lowers uric acid levels ( 41 ). Similarly, serum uric acid was positively correlated with PTH levels ( 39 , 42 ).…”
Section: Discussionmentioning
confidence: 94%
“…The current study found that CKD patients with gout have higher prevalences of CKDmetabolic bone disease and degenerative joint disease, indicating that these patients may be particularly vulnerable to bone and joint damage. Prior studies reported higher PTH levels with hyperuricemia in patients with [22][23][24] and without [24][25][26] CKD, possibly due to the suppression of 1α-hydroxylase [27]. However, the causative factor in this relationship remains unclear as PTH may inhibit renal urate excretion [24].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, SUA might exert adverse effects on bone health by affecting 1,25D and PTH levels. Several studies have emphasized the inverse correlation between 1,25D concentrations and SUA in hyperuricemic rats 47 and in patients with CKD 48 , 49 , and this association could be reversed after receiving allopurinol to lower SUA levels 49 . Likewise, two observational studies showed that SUA was positively correlated with PTH levels 47 , 50 .…”
Section: Discussionmentioning
confidence: 99%